1999
DOI: 10.1161/01.cir.99.23.2993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pacing Chamber and Atrioventricular Delay on Acute Systolic Function of Paced Patients With Congestive Heart Failure

Abstract: Background-Previous studies of pacing therapy for dilated congestive heart failure (CHF) have not established the relative importance of pacing site, AV delay, and patient heterogeneity on outcome. These variables were compared by a novel technique that evaluated immediate changes in hemodynamic function during brief periods of atrial-synchronous ventricular pacing. Methods and Results-Twenty-seven CHF patients with severe left ventricular (LV) systolic dysfunction and LV conduction disorder were implanted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
374
2
13

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,027 publications
(413 citation statements)
references
References 23 publications
24
374
2
13
Order By: Relevance
“…Myocardial relaxation is influenced by chamber load and homogeneity of activation. [15][16][17][18] In previous work, we did not find an improvement in ventricular relaxation with resynchronization therapy, 4 and Auricchio et al 5 found that CRT had only a modest effect on relaxation. This may, however, reflect the more complex influence of Figure 3.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Myocardial relaxation is influenced by chamber load and homogeneity of activation. [15][16][17][18] In previous work, we did not find an improvement in ventricular relaxation with resynchronization therapy, 4 and Auricchio et al 5 found that CRT had only a modest effect on relaxation. This may, however, reflect the more complex influence of Figure 3.…”
Section: Discussionmentioning
confidence: 60%
“…Such studies have been performed in patients with sinus rhythm and with an existing intraventricular conduction defect. 4,5,9 The mechanisms by which LV-only pacing works remain somewhat controversial. 10 Fusion with electrical activity from the AV node is a possibility [11][12][13] ; however, experimental data have suggested that electrical synchrony is not a prerequisite for mechanical synchrony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at present 30% of patients fail to respond clinically through improved quality of life, exercise capacity and New York Heart Association (NYHA) functional classification of HF and up to 50% show no beneficial changes in cardiac function [3]. Suboptimal LV lead position is a common culprit when evaluating poor outcomes after CRT [47]. Equally, several groups have reported enhanced response rates when targeting tissue which displays evidence of favorable viability [811] or advantageous mechanical [1218] or electrical [1923] properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 Following encouraging results from acute haemodynamic studies, [3][4][5][6] several groups initiated pilot studies of permanent biventricular pacing. 7 8 Results from those open, non-randomised trials were encouraging, revealing a significant improvement in New York Heart Association (NYHA) functional classification, exercise tolerance, and quality of life in those patients.…”
mentioning
confidence: 99%